Genotype/phenotype analysis in Chinese laminin‐α2 deficient congenital muscular dystrophy patients. (31st March 2014) - Xiong, H.; Tan, D.; Wang, S.; Song, S.; Yang, H.; Gao, K.; Liu, A.; Jiao, H.; Mao, B.; Ding, J.; Chang, X.; Wang, J.; et al.
<x xml:space="preserve">Abstract</x> Laminin‐α2 deficient congenital muscular dystrophy (CMD) is an autosomal recessive disorder characterized by severe muscular dystrophy, which is typically associated with abnormal white matter. In this study, we assessed 43 CMD patients with typical white matter abnormality and laminin‐α2 deficiency (complete or partial) diagnosed by immunohistochemistry to determine the clinical and molecular genetic characteristics of laminin‐α2 deficient CMD. LAMA2 gene mutation analysis was performed by direct sequencing of genomic DNAs. Exonic deletion or duplication was identified by multiplex ligation‐dependent probe amplification (MLPA) and verified by high‐density oligonucleotide‐based CGH microarrays. Gene mutation analysis revealed 86 LAMA2 mutations (100%); 15 known and 37 novel. Among these mutations, 73.9% were nonsense, splice‐site or frameshift and 18.8% were deletions of one or more exons. Genetic characterization of affected families will be valuable in prenatal diagnosis of CMD in the Chinese population.